Implementing Character Education through Integrated Social Science Learning to Shape Junior High School Students' Social Character - Nuris Shofatul Fikroh; Nainul Fauziah; Abdul Basith (Indonesian Journal of Character Education Studies, 2025)
Background: Character education plays a vital role in shaping students’ behavior and attitudes, particularly in the development of social character during adolescenceSocial Science, as a subject that discusses human relationships and social phenomena, serves as a strategic medium for internalizing character values. Objective: This study aims to examine the implementation of character education through integrated Social Science learning in shaping the social character of junior high school students. Method: A descriptive qualitative approach was employed in this study, which was conducted at Al Hasib Junior High School, Pakis District, Malang Regency in 2024. Data collection techniques included interviews, observations, and documentation. Data were analyzed using Miles and Huberman’s interactive model, which consists of data reduction, data display, and conclusion drawing. Data validity was ensured through triangulation of time and technique. Result: The findings show that the implementation of character education at Al Hasib Junior High School is conducted through three main school programs: (1) curriculum development that integrates character values into learning materials; (2) extracurricular and school-wide activities designed to cultivate students' social behavior; (3) evaluation mechanisms to assess character development; and (4) the application of core character pillars. Overall, these efforts align with the guidelines issued by the Indonesian Ministry of Education and Culture. Conclusion: Integrated Social Science learning can be effectively utilized as a vehicle for character education, especially in fostering social character among junior high school students. The structured programs and institutional policies at Al Hasib Junior High School have successfully supported this educational goal. Contribution: This study provides practical insights for educators and school policymakers into how character education can be systematically implemented through subject-based learning. It serves as a reference for schools aiming to integrate character values into their curriculum and build a strong social foundation in their students.